Geocaching in Antarctica: heroic exploration for the digital era? - Frame, B; Leane, E; Lindeman, RW (The Polar Journal, 2018)
Trends in digitisation such as virtual reality, citizen science, and big data will impact both tourism and research outreach in Antarctica. We examine one modest but revealing example: geocaching. In particular we review the form and distribution of current geocaching practice in Antarctica and situate that within a global context. Through a self-reflexive examination of our own experiences on Ross Island in the 2018 summer season, we explore some of the ways that digitisation impacts on recreation in Antarctica through our different research lenses. Among other things, we found that geocaching folded into our personal experiences an unanticipated echo of the Heroic Era. Although it is simply our own observations as researchers that we draw on here, we consider that they are usefully suggestive when it comes to the future of human activity in Antarctica as it responds to increasing digitization and to calls for increased public science engagement activity.